A relação estado e sociedade civil: uma análise crítica apartir do marco regulatório das organizações da sociedade civil no município do Jaboatão dos Guararapes - Brito, Mayara (2023)
The year 2016 marks the beginning of a context of complexification of strategies for maintaining capitalist supremacy, which triggered events in the political, economic and ideological spheres, which began to compose ultraneoliberalism, which, among its forms of materialization, ostensibly intensifies the reduction of state responsibility for social policies, with emphasis on the effectiveness of Social Assistance. These Events are contemporaneous with the beginning of the Regulatory Framework for Civil Society Organizations (MROSC) and, in terms of the territory covered, with the conservative and right-wing management of the executive of the municipality of Jaboatão dos Guararapes. In view of the singularities of the situation presented here and the potential consequences of these consequences, this study proposes, from a critical-dialectic perspective, to analyze the (in)compatibilities between public call notices for the area of Social Assistance, regulated by the MROSC as a mediator of the relationship between the State and Civil Society, and the precepts of the theoretical-political and legal frameworks that instruct the public offer of such a policy. Thus, the analysis carried out, making use of a reading of the facts in perspective of totality, through Bibliographic and Documentary Research, the latter centered on Public Call Notices for social assistance services in that municipality, the main findings indicate that the applicability of the MROSC in an ultraneoliberal context characterizes it as yet another mechanism for the State's lack of responsibility towards social demands and corroborates for the removal of the execution of Social Assistance according to the principles and guidelines provided by law. In this way, the conclusive considerations of this study point to the influence of the MROSC in maintaining the State and Civil Society relationship as being formed by opposite poles, especially in a situation where such a format favors capitalist interests.